Sovereign wealth funds - Saw, Swee-Hock; Low, Linda (Saw Centre financial studies, 2009)
Sovereign Wealth Funds (SWFs) have shifted from quiet conservatism to being able and willing to make high-profile investments abroad. With professional discretion and strategy, while being somewhat brand-conscious, they seem to drive a hard bargain to negotiate for value, embarking on acquisitions from financial to technology. However, the 2007 US sub-prime crisis triggered wariness, creating a position of weakness requiring unprecedented bailouts for Western industries, and consequent fire-sales for well-resourced SWFs. This book provides an easy read into the development of traditional SWFs to the new SWFs with illustrated details on investments by SWF by region, sector asset classes and merger and acquisition activities. It also highlights the controversies surrounding SWFs and the guiding behavioural principles in the form of legal, investment, risk management, institutional framework and governance structure for SWFs.